Limitations in Applying State Recognition Theory to Post-Colonial States: The Case of Indonesia - Rifqy Tenribali Eshanasir (Fakultas Hukum Universitas Gadjah Mada, 2026)
This research asserts limitations regarding the applicability of constitutive and declaratory statehood theory, as well as this theoretical dichotomy itself, to the realities of post-colonial states’ struggles for recognition. It selects Indonesia’s 1945-1950 struggle as its case study, which entails political discretion and the pursuit of legal statehood criteria – characteristic of constitutive and declaratory recognition theories respectively. It utilises historical and doctrinal methods, analysing legal texts, academic works on statehood recognition theory, and historical records for consistencies and discrepancies between the theories above and the timeline of Indonesia’s struggle for recognition. It finds that despite claiming to be dichotomous, evidence of both constitutive and declaratory statehood recognition theories are present in Indonesia’s case. Constitutive recognition theory is affirmed insofar as the Netherlands’ use of Eurocentric standards of civilisation to contest Indonesian statehood through invasions and diplomacy, and the US “big stick diplomacy” to coerce the Netherlands into recognising Indonesia. Yet, the same case also affirms declaratory recognition theory, including Indonesia’s pursuit of recognition from Arab League nations and implication as a state via admission into United Nations Security Council meetings. This research concludes Indonesia’s recognition struggle displays how the constitutive-declaratory dichotomy itself has limitations, as evidence of both theories